2013
DOI: 10.5334/jbr-btr.402
|View full text |Cite
|
Sign up to set email alerts
|

Selective arterial embolization for control of haematuria secondary to advanced or recurrent transitional cell carcinoma of the bladder

Abstract: Aim: haematuria is a common symptom in patients with advanced transitional cell carcinoma of the bladder. We report our experience of selective pelvic embolization using gelfoam as an embolic agent to treat intractable haematuria in these patients. Methods: Three male patients aged 66-79 (mean 73.6 years) with inoperable or recurrent transitional cell carcinoma of the bladder underwent selective embolization to treat haematuria over a 9 month period. Initial pathological tumour stages were T2, T3, and T3a. Gel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 9 publications
(12 reference statements)
1
7
0
Order By: Relevance
“…The definition of success differed between studies. Some studies defined success as control and no recurrence of haematuria, with the success rate ranging from 43% [10] , [13] up to 100% [1] , [15] , [22] . Korkmaz et al [15] , subdivided the success rate into clinical success, control of haematuria, and technical success.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The definition of success differed between studies. Some studies defined success as control and no recurrence of haematuria, with the success rate ranging from 43% [10] , [13] up to 100% [1] , [15] , [22] . Korkmaz et al [15] , subdivided the success rate into clinical success, control of haematuria, and technical success.…”
Section: Resultsmentioning
confidence: 99%
“…Some studies focused on the need for blood transfusion as an indicator of success [22] , whilst others focused on haemoglobin and haematocrit levels [15] . Halpenny et al [22] reported that the mean transfusion requirement was 8.6 units before embolisation and 0.3 units after embolisation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Continuous bladder irrigation and washouts, and multiple blood transfusions are not effective in all cases, and any surgery may be associated with significant morbidity. 2 In patients who have already undergone radical radiotherapy, such as this patient in the form of a permanent prostate brachytherapy, further palliative radiotherapy is not considered beneficial. Angiographic embolization represents an alternative safe and effective means of achieving haemostasis in this population.…”
Section: Discussionmentioning
confidence: 99%
“…Preliminary studies have demonstrated the short- and medium-term efficacy of selective embolization in controlling refractory vesical haemorrhage secondary to radiation cystitis, 3 prostatic disease, 4 as well as gynaecological 5 and bladder 2 malignancy. Success rates of this treatment modality varied between 75% and 100%, depending on the study.…”
Section: Learning Pointsmentioning
confidence: 99%